AMPEROMETRIC DETERMINATION OF PALLADIUM(II) BY N,N-DIPHENYL- AND N,N'-DIPHENYLTHIOUREAS (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Interaction of palladium(II) with N,N-diphenyl- and N,N'-diphenylthioureas has been studied by means of amperometric titration method. Passing of the reactions has been recorded with Pd(II):R=l:2 and Pd(II):R=l:4 molar ratio between the reacted components. Determination of the palladium(II) is possible within wide concentration range of the sulphuric and hydrochloric acids. Statistical mathematical treatment of the experimental data has been carried out. Technique for amperometric determination of the palladium using the above-mentioned reagents has been elaborated and applied for its determination in the palladium-plating electrolyte.
Keywords: determination of palladium; sulphuric and hydrochloric acids; amperometric titration method